Study of Strength Improvement in Clayey Soil on Addition of Lime and Old Waste Rubber Tyre Chips - Jagdeep Singh Gahir, Sandeep Singh (International Journal of Advanced Science and Technology, 2020)
To Construct an engineering structures on clayey soil is unsafe due to its low load bearing capacity so for the safe construction of an engineering structure on clayey soil, improvement in bearing capacity of soil is must as clayey soil exhibit expansive. In this study, combined action of lime and old waste rubber tyre chips has been investigated. For the same, a series of experiment have been conducted in laboratory. The different proportions of lime and rubber tyre chips have been added in clayey soil and various properties of soil compared with reference soil sample which include OMC (Optimum Moisture Content), MDD (Maximum Dry Density) and CBR (California Bearing Ration Test. The overall test results indicated that lime with old waste rubber tyre chips is effective in strength improvement of clayey soil.